Wonder as Feminist Pedagogy: Disrupting Feminist Complicity with Coloniality. Issue 1 (July 2021) - Ramos, Fabiane; Roberts, Laura
This article documents our collaborative ongoing struggle to disrupt the reproduction of the coloniality of knowledge in the teaching of Gender Studies. We document how our decolonial feminist activism is actualised in our pedagogy, which is guided by feminist interpretations of 'wonder' (Irigaray, 1999; Ahmed, 2004; hooks, 2010) read alongside decolonial theory, including that of Ramón Grosfoguel, Walter D. Mignolo and María Lugones. Using notions of wonder as pedagogy, we attempt to create spaces in our classrooms where critical self-reflection and critical intellectual and embodied engagement can emerge. Our attempts to create these spaces include multiple aspects or threads that, when woven together, might enable other ways of knowing-being-doing that works towards disrupting feminist complicity with coloniality in the Australian context.